Pengaruh Online Customer Review Terhadap Keputusan Berbelanja Online Dengan Trust Sebagai Variabel Mediasi Pada Pengguna Platform Live Shopping Di Kota Padang - Rizki Darmawan; Yofina Mulyanti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study examines the influence of online customer reviews on online purchasing decisions, with trust as a mediating variable, on live shopping platforms in Padang City. Using a quantitative approach, data was collected thru questionnaires distributed to 138 respondents who have experience purchasing products/goods on live shopping platforms. The analysis was conducted using Partial Least Squares (PLS) to assess the direct and indirect relationships between the variables. The research results indicate that online customer reviews do not have a positive and significant impact on online purchasing decisions. Online customer reviews have a positive and significant impact on trust. Trust has a positive and significant impact on purchasing decisions. Trust mediates the relationship between Online Customer Reviews and purchasing decisions